PERISTILAHAN RIBA: SATU ANALISIS HUKUM - Ab Ghani, Ab Mumin (Jurnal Syariah, 2019)
The issue of riba has received serious attention from the ulama right from the days of Sahabah because its forbidance is clear in the Quran and Sunnah. However, the issue continues to arise among the intellectuals and the discussion is centred on the concept of riba itself. What does it actually refer to? Is its forbidence cover all the contemporary financial transactions or is limited only to the practices of the Arabs of the days when the verses were revealed? Because of that there are ulama who suggest that the term riba should be redefined in the context of the modern development. The article tries to look at the issue by evaluating the opinion and arguements of the ulama and how they define riba.